EXPERIMENTAL FORMULATION OF ANTI FOULING PAINT WITH TRIBUTYL TIN OXIDE ASTOXIC PIGMENT - PILLAI, A. G GOPALAKRISHNA; NAIR, N UNNIKRISHNA (Fishery Technology, 2016)
Results of the experimental formulation of ;J.n antifouling paim incorporating TBTO as toxic pigment are presented in this paper. Of the various resins tested, namely, phenolic, cashew nut shell liquid (CNSL), epoxy, li11seed oil with rosin and limed rosin, the paint compositiOn with limed rosin gave the critical leaching rate of TBTOÂ· Acid alkali test showed dissolution of matrix and visible migration of toxin to the surface. Accelerated corrosion tests had not recorded any signs of corrosion in panels painted with or without barier coat. Raft exposure studies indicated that the new formulation could resist fouling accumulation on painted panels for 9 months.